Vínculos que atravessam as ruas : uma análise de condições de vulnerabilidade social entre adolescentes com trajetória de rua em cumprimento de medidas socioeducativas - Mateus Ribeiro de Oliveira Gonçalves (2022)
This work is theoretically located among studies that address issues on social vulnerability and public policies, including discussions on poverty, social exclusion, vulnerable children and adolescents, violence and crime, juvenile delinquency and homelessness. A document analysis and content analysis were carried out based on 23 reports of Individual Care Plans (IAPs), aimed at monitoring adolescents in compliance with socio-educational measures who have in common experiences on the streets throughout their lifes. Such documents were made available by the Centro Integrado de Atendimento ao Adolescente Autor de Ato Infracional de Belo Horizonte (CIA-BH). From their analyses, 50 categories related to six main dimensions of analysis identified in the corpus of analyzed documents were constructed. Such dimensions were 1 - Fragility of family ties (eleven categories), 2 - "Fragility of community ties" (nine categories), 3 - "Fragility of school ties" (eleven categories), 4 - "Involvement in work activities" (five categories), 5 – “Causes, motivation and influences for moving to the street environment” (eight categories) and 6 – “Elements present in the daily life of adolescents during their stay in the street environment” (six categories). The aspects identified pointed to weaknesses in essential bonds for the integration of adolescents monitored by the PIAs teams, configuring a process of progressive social vulnerability that is reflected in the direction of these individuals to the street situation and in vulnerable experiences in this environment. This work directs considerations about the importance of initiatives aimed at strengthening bonds and building perspectives beyond the context of vulnerability experienced by these adolescents in their processes of protection and social integration.